Objective and subjective evaluation of voice quality in multiple sclerosis - MİDİ, İPEK (MOSBY-ELSEVIER, 2007)
The aim of this comparative, controlled, cross-sectional study is to evaluate the voice quality in patients with multiple sclerosis (MS) by subjective and objective methods. Female patients with MS (n = 27) and age- and sex-matched healthy controls (n = 27) were included in this study. Vocal functions were evaluated by a multidimensional set composed of videolaryngostroboscopic examination, acoustic analysis, and subjective measurements (GRBAS and Voice Handicap Index). Jitter percent, shimmer percent, and soft phonation index (SPI) values were higher in MS patients compared to controls (Jitt, P = 0.001; Shim, P = 0.033; SPI P < 0.0001). Maximum phonation time was significantly shorter for MS patients compared to controls (P < 0.0001). Stroboscopic examination revealed that 16 out of 27 MS patients have a posterior chink as glottic closure pattern with higher SPI values (40%). Noise to harmonic ratio (NHR) and mean fundamental frequency (F-0) values were similar for MS and control groups (NHR, P = 0.737; F-0, P = 0.976). In this study, most of the MS patients had dysphonia due to weakness of voice. MS tends to worsen acoustic parameters including fundamental frequency, SPI, and jitter values. These results are consistent with the more asthenic voice quality observed in MS group.
Keywords: multiple sclerosis; voice analyses; dysphonia; ACOUSTIC ANALYSIS; INDIVIDUALS; DISEASE; SPEECH